Spatially enriched paralog rearrangements argue functionally diverse ribosomes arise during cold acclimation in arabidopsis - Martínez Seidel, Federico; Beine-Golovchuk, Olga; Hsieh, Yin-Chen; Eshraky, Kheloud El; Gorka, Michal; Cheong, Bo-Eng; Jimenez-Posada, Erika V.; Walther, Dirk; Skirycz, Aleksandra; Roessner, Ute; Kopka, Joachim; Pereira Firmino, Alexandre Augusto (International journal of molecular sciences, 2021)
Ribosome biogenesis is essential for plants to successfully acclimate to low temperature. Without dedicated steps supervising the 60S large subunits (LSUs) maturation in the cytosol, e.g., Rei-like (REIL) factors, plants fail to accumulate dry weight and fail to grow at suboptimal low temperatures. Around REIL, the final 60S cytosolic maturation steps include proofreading and assembly of functional ribosomal centers such as the polypeptide exit tunnel and the P-Stalk, respectively. In consequence, these ribosomal substructures and their assembly, especially during low temperatures, might be changed and provoke the need for dedicated quality controls.